Cathode carbon nanosheet of fast-charging sodium-ion battery as well as preparation method and application of cathode carbon nanosheet

The preparation of oxysulfur co-doped mesoporous carbon nanosheets by heat treatment of materials such as gluconate and thiourea has solved the problems of low Coulomb efficiency and poor cycle stability of the negative electrode materials of sodium ion battery, and achieved high specific surface area and uniform layer spacing, which improved the charge and discharge performance and cycle life of sodium ion battery.

CN120553689AActive Publication Date: 2025-08-29CHONGQING INST OF NEW ENE STOR MATER & EQUIP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510581220.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-07
Publication Date
2025-08-29
Estimated Expiration
2045-05-07

AI Technical Summary

Technical Problem

The existing sodium ion battery negative electrode materials have problems of low Coulomb efficiency and poor cycle stability for the first time, especially the small layer spacing of hard carbon materials leads to poor sodium ion kinetic performance, and the soft carbon materials have low reversible capacity during sodium storage.

Method used

Gluconate is used as a carbon source and oxygen source, combined with N and S-containing organic matter such as thiourea, and co-doped mesoporous carbon nanosheets are formed by heat treatment, and a large number of pores and active sites are formed by gas expansion and hybridization decomposition, which improves the specific surface area and layer spacing of the material, and enhances the reaction kinetics of sodium ions.

Benefits of technology

The prepared negative electrode carbon nanosheets reached 83.9% in the first round of the Coulomb efficiencies at 0.1C, and cycled more than 10,000 times at a high ratio of 20C, showing excellent electrical performance and long cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120553689A_ABST
    Figure CN120553689A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a fast-charging sodium-ion battery negative electrode carbon nanosheet, which comprises the following steps: 1) uniformly mixing gluconate, a pore-forming agent and an organic matter containing N and S, and then carrying out heat treatment; and 2) uniformly grinding the primary carbonized product, performing heat treatment again, and then performing washing and vacuum drying. According to the negative electrode carbon nanosheet, gluconate is adopted as a carbon source, an oxygen source and an in-situ template agent, CO2, SO2, NO2 and other gases generated in the hybridization decomposition process of a sulfur source and alkali metal bicarbonate at a high temperature are utilized, the interlayer spacing of carbon is optimized, and the prepared negative electrode carbon nanosheet has excellent electrical properties in a sodium ion half-cell; and the coulombic efficiency of the first circle reaches 83.9% under the 0.1 C multiplying power. After full activation, the reversible specific capacity is stabilized at about 340mAh / g under the current density of 0.5 C, and the material can work at the high rate of 20C and can circulate for more than 10000 circles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of battery materials, and specifically relates to a fast-charging sodium ion battery negative electrode carbon nanosheet and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (SIBs) are widely used in commercial electronics and electric vehicles due to their high energy density, long cycle life, and lack of memory effect. However, due to the limited and uneven distribution of lithium resources and the poor safety performance of lithium-ion batteries, alternative battery systems are needed to meet energy needs. Sodium ions are located in the same main group as lithium ions in the periodic table. Sodium-ion batteries (SIBs) share the same rocking-chair operating principle as lithium-ion batteries, allowing them to use similar components. Furthermore, SIBs offer advantages such as abundant sodium resources (the content of sodium in the Earth's crust is 440 times that of lithium), fast charging performance, excellent low-temperature performance, and low cost, making them a promising alternative to lithium-ion batteries.

[0003] The performance of sodium-ion batteries is largely determined by the anode, and current carbon-based sodium-ion anodes are primarily based on amorphous carbon materials. Amorphous carbon has a highly disordered microstructure, large interlayer spacing, numerous surface defects, and nanopores formed by overlapping graphite crystallites, providing numerous reaction sites for sodium storage. Amorphous carbon materials can be divided into two categories: hard carbon and soft carbon (carbon materials that can graphitize above 2800°C are called soft carbon, while those that cannot are hard carbon). Hard carbon has a closed-pore structure and abundant defects, allowing sodium ions to intercalate and deintercalate between its layers, exhibiting either an adsorption / insertion or adsorption / filling mechanism during sodium storage. Furthermore, its excessively disordered graphite layers lead to poor electrical conductivity. For these reasons, hard carbon suffers from poor rate performance and low initial coulombic efficiency during sodium storage. In contrast, soft carbon has a higher degree of graphitization and better electrical conductivity. It also exhibits adsorption and desorption behavior at surface defects during sodium storage, making sodium ions more easily intercalated and deintercalated during charge and discharge. Therefore, soft carbon has great potential in the application of negative electrode materials in sodium ion batteries.

[0004] Although soft carbon has good rate performance, its small interlayer spacing is not conducive to the kinetics of sodium ions, resulting in low reversible capacity. To address this issue, current research focuses on increasing the interlayer spacing through heteroatom doping. However, the excessive macropore content of the material is not conducive to sodium storage. At the same time, excessive side reactions will consume some sodium ions, resulting in irreversible capacity loss in the first cycle and a low first coulombic efficiency. Summary of the Invention

[0005] The present invention aims to at least partially address one of the technical problems in the related art. To this end, the main purpose of the present invention is to provide a fast-charging sodium-ion battery anode carbon nanosheet, aiming to address the low initial coulombic efficiency and poor cycling stability of existing heteroatom-doped anode carbon materials.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet comprises the following steps:

[0008] 1) uniformly mixing gluconate, a pore-forming agent, and an organic matter containing N and S, followed by heat treatment to obtain a preliminary carbonized product;

[0009] 2) The preliminary carbonized product in step 1) is ground uniformly, heat-treated again, and then washed and vacuum-dried to obtain negative electrode carbon nanosheets.

[0010] In the preparation method of the present invention, first, gluconate is used as a carbon source, an oxygen source and an in-situ template. After decomposition, sodium oxides or sodium salts such as (NaO, Na2CO3) are generated. These substances act as templates in the carbonization process. After being washed away, a large number of pores are left. The pore size distribution is between 1.8-5nm, which is mesoporous. At the same time, the introduction of a large number of pores will also increase the specific surface area of ​​the material. Then, during the initial carbonization process, sodium bicarbonate decomposes to produce a large amount of CO2 and H2O, which play an expansion role and increase the specific surface area of ​​the material. At the same time, organic matter containing N and S (thiourea) will also initially decompose to produce gases such as sulfur oxides, nitrogen oxides, and carbon oxides such as H2S and NH3, which will cause the material after initial carbonization to expand further and further increase the specific surface area; further, at high temperature (second heat treatment), the graphite layer continues to grow, and thiourea and sodium carbonate continue to hybridize and decompose. The SOx, NOx, and COx produced by the decomposition of thiourea will induce the formation of more sites in the pores, resulting in defects and making the interlayer spacing distribution of carbon more uniform. A large amount of gas will also increase the number of mesopores, further increasing the specific surface area of ​​the material; and at high temperature (second heat treatment), the SOx, NOx, etc. produced by the decomposition of thiourea will bond with carbon during the carbonization process to form active sites, reduce the adsorption energy of sodium ions, and thus improve the reaction kinetics of sodium ions.

[0011] In certain embodiments, the gluconate includes but is not limited to any one or more of sodium gluconate, potassium gluconate, potassium gluconate and zinc gluconate.

[0012] In certain embodiments, the pore-forming agent includes but is not limited to alkali metal bicarbonate, and the alkali metal bicarbonate includes but is not limited to any one or more of sodium bicarbonate, ammonium bicarbonate, potassium bicarbonate, and calcium bicarbonate.

[0013] In certain embodiments, the N and S-containing organic matter includes, but is not limited to, any one or more of thiourea, thioamino acid, and acetyl thioester.

[0014] In certain specific embodiments, the mass ratio of the pore-forming agent, the organic matter containing N and S, and the gluconate is (0.1-1):(0.1-2):1.

[0015] In certain specific embodiments, the process conditions of the heat treatment in step 1) are: heat treatment temperature is 300-400° C., and time is 0.5-1 h.

[0016] In certain specific embodiments, the process conditions of the heat treatment in step 2) are: the heat treatment temperature is 600-1000° C., and the time is 1-3 hours; and the vacuum drying is drying at a drying temperature of 100-130° C. for 10-12 hours.

[0017] In certain specific embodiments, the mixing in step 1) specifically includes ethanol, with 2-3 ml of ethanol added per gram of gluconate. This step facilitates uniform dispersion of the gluconate, pore-forming agent, and N- and S-containing organic matter, providing technical support for subsequently obtaining negative electrode carbon nanosheets with uniform pore size distribution.

[0018] As the same inventive concept, the present invention also provides a fast-charge sodium ion battery negative electrode carbon nanosheet prepared by the preparation method, wherein the negative electrode carbon nanosheet is a block structure with a particle size of 2-20 μm, a pore size of 1.8-5 nm, and a specific surface area of ​​1000-1700 m 2 / g, and the average carbon layer spacing is 0.41-0.45nm.

[0019] As the same inventive concept, the present invention also provides the application of the fast-charging sodium ion battery negative electrode carbon nanosheet in a sodium ion battery.

[0020] Compared with the prior art, the present invention has at least the following advantages:

[0021] 1) The negative electrode carbon nanosheets of the present invention use gluconate as a carbon source, oxygen source and in-situ template agent, and utilize the CO2, SO2, NO2 and other gases generated during the hybrid decomposition process of sulfur source and alkali metal bicarbonate at high temperature to optimize the carbon interlayer spacing and prepare nitrogen, oxygen and sulfur co-doped mesoporous carbon nanosheets with high specific surface area. The negative electrode carbon nanosheets have a pore size of 1.8-5nm and a specific surface area of ​​1000-1700m 2 / g, with an average carbon interlayer spacing of 0.41-0.45nm, which is conducive to the insertion and extraction of sodium ions. The induced active sites (CS, CO, CN, etc.) generated from the oxygen and nitrogen and sulfur sources in the template are responsible for the excellent electrical performance of this material in sodium-ion half-cells, with a first-cycle coulombic efficiency of 83.9% at a rate of 0.1C. After full activation, its reversible specific capacity stabilizes at around 340mAh / g at a current density of 0.5C. Even at a high rate of 20C, it can cycle for over 10,000 cycles, demonstrating both high rate and long cycle life.

[0022] 2) The negative electrode carbon nanosheets of the present invention have a sheet and / or block structure with a particle size distribution of 2-20 μm. The abundant defects and pores on the surface provide more reaction sites and transmission paths for sodium ions. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific embodiments of the present invention, the following briefly introduces the drawings required for the specific embodiments or the description of the prior art.

[0024] Figure 1 XRD results of the nitrogen, oxygen and sulfur doped mesoporous negative electrode carbon nanosheets with a ratio of sodium gluconate: thiourea: sodium bicarbonate = 2:0.75:1 provided in Example 1 of the present invention;

[0025] Figure 2 XRD results of the nitrogen, oxygen and sulfur doped mesoporous negative electrode carbon nanosheets with a ratio of sodium gluconate: thiourea: sodium bicarbonate = 2:0.5:1 provided in Example 2 of the present invention;

[0026] Figure 3 XRD results of the nitrogen, oxygen and sulfur doped mesoporous negative electrode carbon nanosheets with a ratio of sodium gluconate to sodium bicarbonate of 2:1 provided in Comparative Example 1 of the present invention;

[0027] Figure 4 This is an SEM image of the nitrogen, oxygen and sulfur doped mesoporous negative electrode carbon nanosheets with a ratio of sodium gluconate: thiourea: sodium bicarbonate = 2:0.75:1 provided in Example 1 of the present invention;

[0028] Figure 5 This is an SEM image of the nitrogen, oxygen and sulfur doped mesoporous negative electrode carbon nanosheets with a ratio of sodium gluconate: thiourea: sodium bicarbonate = 2:0.5:1 provided in Example 2 of the present invention;

[0029] Figure 6 This is the SEM result of the mesoporous negative electrode carbon nanosheet with a ratio of sodium gluconate to sodium bicarbonate of 2:1 provided in Comparative Example 1 of the present invention;

[0030] Figure 7BET result diagram of nitrogen, oxygen and sulfur doped mesoporous negative electrode carbon nanosheets with a ratio of sodium gluconate: thiourea: sodium bicarbonate = 2:0.75:1 provided in Example 1 of the present invention;

[0031] Figure 8 BET result diagram of nitrogen, oxygen and sulfur doped mesoporous negative electrode carbon nanosheets with a ratio of sodium gluconate: thiourea: sodium bicarbonate = 2:0.5:1 provided in Example 2 of the present invention;

[0032] Figure 9 This is a BET result diagram of the mesoporous negative electrode carbon nanosheet with a ratio of sodium gluconate to sodium bicarbonate of 2:1 provided in Comparative Example 1 of the present invention;

[0033] Figure 10 This is a rate performance diagram of the negative electrode carbon nanosheet with a ratio of sodium gluconate: thiourea: sodium bicarbonate = 2:0.75:1 provided in Example 1 of the present invention;

[0034] Figure 11 The cycling performance of the sodium ion battery using the negative electrode carbon nanosheets in Example 1 as the negative electrode material at 20C. DETAILED DESCRIPTION

[0035] The present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are merely illustrative and non-restrictive, and should not be used to limit the scope of protection of the present invention.

[0036] When expressing a certain amount, concentration or other value or parameter in the form of a range, preferred range, or preferred upper and lower numerical limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper range limits or preferred numerical values ​​with any lower range limit or preferred numerical value, without considering whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values ​​listed herein are inclusive of the endpoints of the range and all integers and fractions within the range.

[0037] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0038] The materials, methods, and examples herein are illustrative and, unless otherwise indicated, are not to be construed as limiting.

[0039] In the following examples, all materials were of analytical purity. Sodium gluconate and calcium gluconate were purchased from Tianjin Zhonglian Chemical Reagent Co., Ltd., thiourea was purchased from Aladdin Chemical Reagent Co., Ltd., and sodium bicarbonate was purchased from Sinopharm Chemical Reagent Co., Ltd.

[0040] Example 1

[0041] This embodiment provides a method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet, which includes the following steps:

[0042] 1) Sodium gluconate, sodium bicarbonate, and thiourea were mixed in a mass ratio of 2:1:0.75, and 2.5 ml of anhydrous ethanol was added per 1 g of sodium gluconate. The mixture was then ground under an infrared lamp until dry to obtain a precursor;

[0043] 2) placing the precursor in step 1) in a muffle furnace and heating the temperature to 400° C. at a heating rate of 10° C. / min and then maintaining the temperature for 0.5 h to obtain a preliminary carbonized product;

[0044] 3) grinding the preliminary carbonized product in step 2) uniformly again, heating to 900° C. at a heating rate of 5° C. / min under an argon atmosphere, and then maintaining the temperature for 2 h to obtain a pyrolysis product;

[0045] 4) The pyrolysis product in step 3) was repeatedly washed with deionized water until neutral, dried in a forced air drying oven, and then dried in a vacuum oven at 120° C. for 10 h to obtain the negative electrode carbon nanosheets.

[0046] Example 2

[0047] This embodiment provides a method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet, which includes the following steps:

[0048] 1) Sodium gluconate, sodium bicarbonate, and thiourea were mixed in a mass ratio of 2:1:0.5, and 2.5 ml of anhydrous ethanol was added per 1 g of sodium gluconate. The mixture was then ground under an infrared lamp until dry to obtain a precursor;

[0049] 2) placing the precursor in step 1) in a muffle furnace and heating the temperature to 400° C. at a heating rate of 10° C. / min and then maintaining the temperature for 0.5 h to obtain a preliminary carbonized product;

[0050] 3) grinding the preliminary carbonized product in step 2) uniformly again, heating to 900° C. at a heating rate of 5° C. / min under an argon atmosphere, and then maintaining the temperature for 2 h to obtain a pyrolysis product;

[0051] 4) The pyrolysis product in step 3) was repeatedly washed with deionized water until neutral, dried in a forced air drying oven, and then dried in a vacuum oven at 120° C. for 10 h to obtain the negative electrode carbon nanosheets.

[0052] Example 3

[0053] This embodiment provides a method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet, which includes the following steps:

[0054] This embodiment provides a method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet, which includes the following steps:

[0055] 1) Calcium gluconate, sodium bicarbonate, and thiourea were mixed in a mass ratio of 2:1:0.5, and 2.5 ml of anhydrous ethanol was added per 1 g of sodium gluconate. The mixture was then ground under an infrared lamp until dry to obtain a precursor;

[0056] 2) placing the precursor in step 1) in a muffle furnace and heating the temperature to 400° C. at a heating rate of 10° C. / min and then maintaining the temperature for 0.5 h to obtain a preliminary carbonized product;

[0057] 3) grinding the preliminary carbonized product in step 2) uniformly again, heating to 900° C. at a heating rate of 5° C. / min under an argon atmosphere, and then maintaining the temperature for 2 h to obtain a pyrolysis product;

[0058] 4) The pyrolysis product in step 3) was repeatedly washed with deionized water until neutral, dried in a forced air drying oven, and then dried in a vacuum oven at 120° C. for 10 h to obtain the negative electrode carbon nanosheets.

[0059] Comparative Example 1

[0060] This comparative example 1 provides a method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet, which is basically the same as that of Example 1, except that thiourea is not added, specifically:

[0061] 1) Sodium gluconate and sodium bicarbonate were mixed in a mass ratio of 2:1, and 2.5 ml of anhydrous ethanol was added per 1 g of sodium gluconate. The mixture was then ground under an infrared lamp until dry to obtain a precursor;

[0062] 2) placing the precursor in step 1) in a muffle furnace and heating the temperature to 400° C. at a heating rate of 10° C. / min and then maintaining the temperature for 0.5 h to obtain a preliminary carbonized product;

[0063] 3) grinding the preliminary carbonized product in step 2) uniformly again, heating to 900° C. at a heating rate of 5° C. / min under an argon atmosphere, and then maintaining the temperature for 2 h to obtain a pyrolysis product;

[0064] 4) The pyrolysis product in step 3) was repeatedly washed with deionized water until neutral, dried in a forced air drying oven, and then dried in a vacuum oven at 120° C. for 10 h to obtain the negative electrode carbon nanosheets.

[0065] Performance Testing

[0066] This application also conducts characterization tests and performance tests on the prepared negative electrode carbon nanosheets, specifically:

[0067] 1) Carbon layer spacing

[0068] The negative electrode carbon nanosheets prepared in Examples 1-2 and Comparative Example 1 were tested using an XRD diffraction instrument. The results are as follows: Figure 1 、 2As shown in Figure 3, the (002) peak positions corresponding to the carbon layer spacing are 21.15°, 20.89°, 20.03° / 26.12°, and the corresponding layer spacings are The carbon material without the addition of thiourea still has a narrow carbon layer, while the carbon material regulated by hybrid decomposition has a more uniform interlayer spacing, and the impurity Na2CO3 produced is easier to wash out.

[0069] 2) Micromorphology

[0070] In this test, the particle size and micromorphology of the negative electrode carbon nanosheets prepared in Examples 1-2 and Comparative Example 1 were measured by SEM. The results are as follows: Figure 4 、 5 As shown in Figures 6 and 7, it can be seen that the negative electrode carbon nanosheets in Example 1 have more surface defects than those in Example 2 and Comparative Example 1. At the same time, the particle size distribution of the materials can be seen. The negative electrode carbon nanosheets in Examples 1 and 2 have smaller particle sizes, with a maximum particle size of approximately 20 μm. The negative electrode carbon nanosheets in Example 1 have a sheet-like structure, while the negative electrode carbon nanosheets in Example 2 have a block-like structure. The maximum particle size in Comparative Example 1 is approximately 30 μm, and its negative electrode carbon nanosheets have a block-like structure. That is, the particle size of the negative electrode carbon nanosheets in Example 1 is significantly smaller than that in Comparative Example 1. The smaller particle size increases the specific surface area. At the same time, its sheet-like structure also provides more contact sites for sodium ions, which is beneficial to improving kinetic performance.

[0071] 3) Physical properties

[0072] In this test, the negative electrode carbon nanosheets prepared in Examples 1-2 and Comparative Example 1 were subjected to BET full analysis to explore their specific surface area and pore size distribution. The results are as follows: Figure 7 、 8 As shown in Figure 9, the specific surface areas of the carbon materials with thiourea contents of 0.75, 0.5, and 0 are 1410.7878 m 2 / g,1685.8490m 2 / g,464.8551m 2 / g; its pore diameter is mostly distributed between 1.8-5nm, which is a mesoporous material.

[0073] 4) Element content

[0074] In this test, the nitrogen, oxygen and sulfur contents of the negative electrode carbon nanosheets prepared in Examples 1-2 and Comparative Example 1 were analyzed using EA. The results are shown in Table 1:

[0075] Table 1 Contents of N, C, S and O in the negative electrode carbon nanosheets in each embodiment and comparative example

[0076] N(%) C(%) S(%) O(%) Example 1 3.34 85.38 1.45 6.34 Example 2 0.81 91.63 0.87 5.15 Example 3 2.53 89.06 1.24 5.87 Comparative Example 1 0.15 76.90 0.43 9.92

[0077] From the data in Table 1, it can be seen that as the amount of thiourea increases, the nitrogen and sulfur contents in the negative electrode carbon nanosheets in the present application continue to increase, wherein the doping amount of the negative electrode carbon nanosheets in Example 1 is: N: 3.34wt%, S: 1.45wt%, O: 6.34wt%; in Comparative Example 1, O mainly comes from Na2CO3 or its decomposition products.

[0078] 5) Electrical performance analysis

[0079] This test was conducted on the electrical properties of the negative electrode carbon nanosheets prepared in Examples 1-2 and Comparative Example 1. The specific test method is as follows:

[0080] The negative electrode carbon nanosheets prepared in Example 1, Example 2 and Comparative Example 1 were used to prepare the pole pieces. Specifically, the mass ratio of the slurry is: negative electrode carbon nanosheet: binder (PVDF): conductive agent (Ketjen black) = 8:1:1, and an appropriate amount of N-methylpyrrolidone is added and mixed evenly and then coated on the copper foil. After drying, it is cut into electrode sheets with a diameter of 12 mm, the sodium sheet is the counter electrode, the glass fiber is the diaphragm, and 1M NaPF6 in DIGLYME is the electrolyte to assemble into a CR2032 type button battery. The voltage range of the test is: 0.01-2.8V, and the test temperature is 25°C. The test method is: the first charge and discharge test is carried out at 0.1C, the rate test is carried out at 0.1C, 0.2C, 0.5C, 1C, 2C, 5C, 10C, 20C, 0.1C, and the material is cycled at 20C. The results are shown in Table 2. Figure 10 and Figure 11 As shown:

[0081] Table 2 First efficiency and rate performance of sodium ion batteries using negative electrode carbon nanosheets in various embodiments and comparative examples (mAh / g)

[0082]

[0083] From the data in Table 2, it can be seen that the material properties of the nitrogen, oxygen and sulfur doped mesoporous carbon nanosheets prepared in Examples 1-3 are better than those in Comparative Example 1. Figure 10 As shown, the nitrogen, oxygen and sulfur doped mesoporous carbon nanosheets obtained in Example 1 have the best performance, with the first-cycle coulombic efficiency reaching 83.9%, and the results in the rate test are slightly higher than those in Examples 2-3.

[0084] from Figure 11 It can be seen that the negative electrode carbon nanosheets in Example 1 can still cycle 10,000 times at a high rate of 20C, which shows that the material synthesized by in situ pore formation and hybrid decomposition has a high specific surface area, suitable interlayer spacing, number of mesopores and active sites, etc., which can enable the material to exhibit excellent rate performance and stability in the use of sodium ion batteries.

[0085] However, the negative electrode carbon nanosheets in Comparative Example 1 did not contain thiourea and did not form a good morphology. Although it was also a mesoporous material, the number of mesopores was significantly smaller than that in Examples 1-2, which was not conducive to the reaction and storage of sodium ions. Therefore, the electrochemical performance was poor.

[0086] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.

Claims

1. A method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet, characterized in that: The steps include: 1) uniformly mixing gluconate, a pore-forming agent, and an organic matter containing N and S, followed by heat treatment to obtain a preliminary carbonized product; 2) The preliminary carbonized product in step 1) is ground uniformly, heat-treated again, and then washed and vacuum-dried to obtain negative electrode carbon nanosheets.

2. The method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet according to claim 1, characterized in that: The gluconate includes but is not limited to any one or more of sodium gluconate, potassium gluconate, potassium gluconate and zinc gluconate.

3. The method for preparing the negative electrode carbon nanosheet of a fast-charging sodium ion battery according to claim 1, characterized in that: The pore-forming agent includes but is not limited to alkali metal bicarbonate, and the alkali metal bicarbonate includes but is not limited to any one or more of sodium bicarbonate, ammonium bicarbonate, potassium bicarbonate, and calcium bicarbonate.

4. The method for preparing a fast-charging sodium-ion battery negative electrode carbon nanosheet according to claim 1, characterized in that: The N and S-containing organic matter includes but is not limited to any one or more of thiourea, thioamino acid, and acetyl thioester.

5. The method for preparing the negative electrode carbon nanosheet for fast-charging sodium ion battery according to claim 4, characterized in that: The mass ratio of the pore-forming agent containing N and S organic matter to gluconate is (0.1-1): (0.1-2):

1.

6. The method for preparing a negative electrode carbon nanosheet for a fast-charging sodium ion battery according to claim 1, characterized in that: The process conditions of the heat treatment in step 1) are: heat treatment temperature is 300-400° C., and time is 0.5-1 h.

7. The method for preparing a negative electrode carbon nanosheet for a fast-charging sodium ion battery according to claim 1, characterized in that: The process conditions of the heat treatment in step 2) are: the heat treatment temperature is 600-1000° C., and the time is 1-3 hours; the vacuum drying is drying at a drying temperature of 100-130° C. for 10-12 hours.

8. The method for preparing a negative electrode carbon nanosheet for a fast-charging sodium ion battery according to claim 4, characterized in that: The mixing in step 1) specifically includes ethanol, with 2-3 ml of ethanol added per gram of gluconate.

9. A fast-charging sodium-ion battery negative electrode carbon nanosheet prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The negative electrode carbon nanosheets are block-shaped, with a particle size of 2-20 μm, a pore size of 1.8-5 nm, and a specific surface area of ​​1000-1700 m 2 / g, and the average carbon layer spacing is 0.41-0.45nm.

10. Use of the fast-charging sodium-ion battery negative electrode carbon nanosheet according to claim 9 in a sodium-ion battery.

Citation Information

Patent Citations

  • Preparation method of porous hard carbon material for sodium-ion battery as well as product and application of porous hard carbon material

    CN114988390A

  • Hard carbon material, preparation method and application thereof, and sodium ion battery

    CN117293312A

  • Preparation method of modified asphalt-based hard carbon material for sodium-ion battery

    CN117326544A

  • Chromium-based bimetallic sulfide-porous carbon composite material as well as preparation method and application thereof

    CN119569118A

  • Transition metal compound-hybridized and nitrogen-doped porous carbon material and preparation method therefor

    WO2021238912A1